1992
DOI: 10.1095/biolreprod47.6.945
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Kinin System in the Ovary during Ovulation in the Rat1

Abstract: Ovulation has been noted for some time to bear a remarkable similarity to an inflammatory response. One of the principal components that is activated and helps mediate the events during an inflammatory response is the kinin system. Therefore, the purpose of the present study was to examine whether this system could be similarly activated and involved in the cascade of events that leads to ovulation. To answer this question, immature 23-day-old female rats were primed with eCG (10 IU) and ovulation was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Previous studies have demonstrated an increase in ovarian kinin-producing activity during ovulation [27][28][29]. Moreover, it has been established that BK induces ovulation in perfused rabbit ovaries [30][31][32] and potentiates the action of LH [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated an increase in ovarian kinin-producing activity during ovulation [27][28][29]. Moreover, it has been established that BK induces ovulation in perfused rabbit ovaries [30][31][32] and potentiates the action of LH [33].…”
Section: Discussionmentioning
confidence: 99%
“…This points to the possibility that intrafollicular kallidin (lysyl-BK) might also be produced from LMW-K. A tissue kallikrein is generally thought to catalyze the production of kinin from LMW-K. Several investigators have indeed reported an increase in tissue kallikrein activity [27][28][29]34] with a concomitant elevation of LMW-K [28] in rat ovary extract during ovulation. At present, however, it is not known to what extent the LMW-K/tissue kallikrein system contributes to kinin formation within porcine ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Kallikrein is an active member in the kininogen-kallikreinkinin (K-K-K) system in which kallikrein cleaves kininogen to release the vasoactive peptide, bradykinin [12]. The K-K-K system has been shown to be involved in reproductive functions such as ovulation [13] and implantation in the rat [14]. Corthorn and coworkers [15] demonstrated that estrogens play a role in stimulating kallikrein release.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that bradykinin acts directly on GnRH neurons through a mechanism involving mediation by the bradykinin B 2 receptor. It has already been reported that kinin-producing activity increases during ovulation (Smith & Perks 1983, Espey et al 1989, Gao et al 1992. In a study, Kihara et al (2000) showed the presence of a component of bradykinin and bradykinin-producing system in the porcine ovarian follicle, suggesting its role in early follicular development and ovulation.…”
Section: Introductionmentioning
confidence: 90%